Analysis of a child’s declaration in a court process - Bermúdez Tapia, Manuel (2020)
The condition of legal subjects of minors ends up being annulled because family cases are not properly followed in criminal, civil or constitutional judicial processes. In judicialized family conflicts, minors are limited to only observing the context of violence manifested by their parents. There is no active participation of these due to the limited regulation contained in article 85 of the Code of Children and Adolescents regarding the custody process. Consequently, the condition of human conflict within the process is denatured, and the process of socialization within it is denatured.